A molecular loaded dice: When the π conjugation breaks the statistical addressability of an octastate multimodal molecular switch. (June 2022) - Aidibi, Youssef; Beaujean, Pierre; Quertinmont, Jean; Stiennon, Julien; Hodée, Maxime; Leriche, Philippe; Berthet, Jérôme; Delbaere, Stéphanie; Champagne, Benoît; Sanguinet, Lionel
Abstract: The elaboration of multichromophoric system which can undergo a reversible transformation over more than two different states can be easily performed by the covalent assembly of several identical switching subunits around a central node. However, the selective addressability of each of them still represents a challenging task. This study reports on the elaboration of multichromophoric systems incorporating three identical indolino-oxazolidine (BOX) moieties as multimodal addressable units. Depending of the open/closed oxazolidine ring status of each of them, these systems can be interconverted between four different states in stepwise manner by using indifferently acid addition or electrochemical stimulation. More important, we have demonstrated by using a dissymmetric triarylamine node that the classical statistical BOX opening is broken then reaching a regioselective addressability. The switching of the three identical BOX units differentiated by their π conjugated junction to the central core follows a preferential order leading to the preponderant and successive formation of only four forms over the eight theoretically and equally expected. To provide limitations and outlooks for such strategy, their switching capacities have been rationalized by DFT calculations. Graphical abstract: Image 1 Highlights: The synthesis of new multichomophoric system exclusively based on BOX unit is proposed. These multi-addressable systems can switch between four discrete levels exhibiting distinct optical properties. The BOX opening of such multichromophoric system occur under stimulation in a preferential order